Simultaneous fat‐referenced proton resonance frequency shift thermometry and MR elastography for the monitoring of thermal ablations. Issue 1 (11th December 2019) - Kim, Kisoo; Breton, Elodie; Gangi, Afshin; Vappou, Jonathan
Abstract : Purpose: Simultaneous fat‐referenced proton resonance frequency shift (FRPRFS) thermometry combined with MR elastography (MRE) is proposed, to continuously monitor thermal ablations for all types of soft tissues, including fat‐containing tissues. Fat‐referenced proton resonance frequency shift thermometry makes it possible to measure temperature even in the water fraction of fat‐containing tissues while enabling local field‐drift correction. Magnetic resonance elastography allows measuring the mechanical properties of tissues that are related to tissue structural damage. Methods: A gradient‐echo MR sequence framework was proposed that combines the need for multiple TE acquisitions for the water‐fat separation of FRPRFS, and the need for multiple MRE phase offsets for elastogram reconstructions. Feasibility was first assessed in a fat‐containing gelatin phantom undergoing moderate heating by a hot water circulation system. Subsequently, high intensity focused ultrasound heating was conducted in porcine muscle tissue ex vivo ( N = 4; 2 samples, 2 locations/sample). Results: Both FRPRFS temperature maps and elastograms were updated every 4.1 seconds. In the gelatin phantom, FRPRFS was in good agreement with optical fiber thermometry (average difference 1.2 ± 1°C). In ex vivo high‐intensity focused ultrasound experiments on muscle tissue, the shear modulus was found to decrease significantly by 34.3% ± 7.7% (experiment 1, sample 1), 17.9% ± 10.0% (experiment 2, sample 1), 55.1% ± 8.7% (experiment 3, sample 2), and 34.7% ± 8.4% (experiment 4, sample 2) as a result of temperature increase (Δ T = 22.5°C ± 4.2°C, 14.0°C ± 2.8°C, 14.7°C ± 3.7°C, and 14.5°C ± 3.0°C, respectively). Conclusion: This study demonstrated the feasibility of monitoring thermal ablations with FRPRFS thermometry together with MRE, even in fat‐containing tissues. The acquisition time is similar to non‐FRPRFS thermometry combined with MRE.